Cambios recientes en el cauce y la llanura de inundación del área de confluencia Aragón-Arga (Navarra) - Acín Naverac, Vanesa; Díaz Bea, Elena; Granado García, David; Ibisate González de Matutaco, Askoa; Ollero Ojeda, Alfredo (Geographicalia, 2014)
A diachronic analysis of the evolution of river system using GIS tools has been developed. With georeferenced aerial photographs and orthoimages, has been quantified and mapped both the evolution of channel planform as changes in land uses in the floodplain. The most significant changes are observed between 1966 and 1992. Natural surfaces have been lost and the channel has been stabilized, dramatically from the 80, although some meanders in Aragón river maintain dynamics. Regulatory systems, local defences for each bend and the channelization of Arga are responsible for the natural behaviour deterioration and the process of stabilization and geomorphic simplification.
Keywords: fluvial geomorphology; channel; floodplain; confluence; Aragón river; Arga river.